Meningkatkan Aktivitas Belajar Melalui Pembelajaran Tematik pada Peserta Didik Kelas I SDN Serangsari - Rigiati, Henry Aditia; Hidayat, Riska Kania (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The problem of this research is an attempt to increase students' learning activities through thematic learning in Class I of Serangsari State Elementary School. This research method is a descriptive method, the form of the research is classroom action research and is collaborative in nature, the research subjects are teachers and first grade students at Serangsari State Elementary School, totaling 24 people. This study used direct observation techniques, documentation techniques and observation sheets as data collection tools. The results of research based on observation through thematic learning can increase student learning activities. This shows that the hypothesis which states the implementation of thematic learning in grade 1 of Serangsari State Elementary School can increase students' learning activities. Keywords: Learning Activity, Thematic approach